1989
DOI: 10.1111/j.1600-0447.1989.tb03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and the attempted suicide: An interntional perspective

Abstract: This article reviews ihe scope of suicide and atiempted suicide as public health problems from an international perspective. Socio-demographic trends are analyzed and explanatory theories for international differences proposed. Suicide and attempted Fuicide can be prevented, but the development and evaluation of effective large-scale prevention programs is still in its infancy. Inadequacies in current programs across the world has promoted the establishment of national Task Forces on Suicide Prevention in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
0
10

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(131 citation statements)
references
References 0 publications
5
116
0
10
Order By: Relevance
“…On the other hand, Diekstra et al 5 have reported a declining tendency in Mediterranean and Latin-American countries.…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, Diekstra et al 5 have reported a declining tendency in Mediterranean and Latin-American countries.…”
Section: Introductionmentioning
confidence: 95%
“…2,10,23,37,38]. The high rate of suicidal and depressed patients both in clinical and community surveys support the feasibility of conducting research into depressive disorders, and forms of suicidal and selfinjurious behaviour in Hungary.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of completed suicide in industrial, Westernized countries is reported to be around 12 per 100000 of population (Diekstra, 1989). Lifetime preva-1989) and psychosocial and personality factors (Cross & Hirschfeld, 1986).…”
Section: Introductionmentioning
confidence: 99%